2021
DOI: 10.1038/s41533-021-00250-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to implementing asthma self-management in Malaysian primary care: qualitative study exploring the perspectives of healthcare professionals

Abstract: Asthma self-management is a crucial component of asthma management. We sought to explore healthcare professionals’ (HCPs’) perceptions on barriers to asthma self-management implementation in primary care. We recruited 26 HCPs from six public primary care clinics in a semi-urban district of Malaysia in 2019. The analysis was done inductively. HCPs described barriers that resonated with the “COM-B” behaviour change framework. Capability-related issues stemmed from a need for specific self-management skills train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(74 reference statements)
1
11
0
Order By: Relevance
“…Participants highlighted some important gaps in asthma care by primary care doctors in public health clinics including inadequate assessment of control, little treatment intensification for poorly controlled patients and no provision of asthma education. This corresponds with findings from the recent literature which underscored the challenges contributing to these three gaps 14,15 .…”
Section: Discussionsupporting
confidence: 90%
“…Participants highlighted some important gaps in asthma care by primary care doctors in public health clinics including inadequate assessment of control, little treatment intensification for poorly controlled patients and no provision of asthma education. This corresponds with findings from the recent literature which underscored the challenges contributing to these three gaps 14,15 .…”
Section: Discussionsupporting
confidence: 90%
“…We found some of these, including asthma action plans, were not available in important clinic areas such as the emergency rooms, consultation rooms, and pharmacies. A previous local qualitative study found the main reasons for this were budget constraints and lack of prioritisation 20 . Another local study documented adequate numbers of peak flow metres and PEFR reference charts provided in the clinic, however, there was no spacer or placebo inhalers available for teaching patients 21 .…”
Section: Discussionmentioning
confidence: 98%
“…There was also a poor attitude reported in the patients' respondents in which majority felt that they were for very sick patients; Majority of the patients indicated that the use of PAAPs should be used for the very sick people. The practice was poor even for those few who had these tools; in which from a sample of 52 patients who were found to have a PAAPs card those who used to check for their card at home while low count among the respondents who didn't check their card [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%